Air pollution, cardiorespiratory fitness and biomarkers of oxidative status and inflammation in the 4HAIE study - Cipryan, Lukas; Litschmannova, Martina; Barot, Tomas; Dostal, Tomas; Sindler, Dominik; Kutac, Petr; Jandacka, Daniel; Hofmann, Peter (Scientific reports, 2024)
The aim of this study was to investigate the associations between cardiorespiratory fitness (CRF), long-term air pollution exposure and biochemical markers of oxidative status and inflammation. This is a cross-sectional investigation focusing on biochemical markers of oxidative status and inflammation. Participants were Caucasian (N = 1188; age 18-65 years) who lived for at least 5 years in a high air-polluted (Moravian-Silesian; MS) or low air-polluted (South Bohemia; SB) region of the Czech Republic. Healthy runners and inactive individuals were recruited. A multiple regression analysis was used to explain the relationship between multiple independent variables (CRF, trunk fat mass, sex, socioeconomic status, and region (MS region vs. SB region) and dependent variables (oxidative status, inflammation). CRF, trunk fat mass, age and sex significantly predicted almost all selected markers of oxidative status and inflammation (except GSSG, GSH/GSSG and BDNF). Participants living in the MS region presented significantly higher GPx (by 3.1%) and lower BDNF values (by 4.5%). All other investigated biochemical markers were not significantly influenced by region. We did not find meaningful interactions between long-term air-pollution exposure versus markers of oxidative status and inflammation. However, we showed various significant interactions with sex, age, CRF and body composition. The significant association of living in the high air polluted MS region with the BDNF level warrants further attention.
Keywords: senioři; Cross-Sectional Studies; Inflammation; Air Pollution; vystavení vlivu životního prostředí; mladiství; Česká republika; zánět; Middle Aged; mužské pohlaví; Oxidative Stress; znečištění ovzduší; průřezové studie; Adult; mladý dospělý; Environmental Exposure; Czech Republic; Oxidative status; Young Adult; Cardiorespiratory Fitness; ženské pohlaví; Humans; biologické markery; Trunk fat mass; kardiorespirační zdatnost; lidé středního věku; dospělí; oxidační stres; Biomarkers; Female; Aged; Adolescent; Air pollution; lidé; Male